Electrosynthesis of Oxazol‐2(3H)‐Ones and Diaroylhydrazines from 1, 2‐Dicarbonyl Compounds and Arenediazonium Salts. Issue 16 (28th March 2019) - Barba, Fructuoso; Quirós, Irene; Salgado, Antonio; Batanero, Belen
Abstract: New five‐membered oxazol‐2(3 H )‐one heterocycles and 1, 2‐diaroylhydrazines are obtained in good yield when 1, 2‐dicarbonyl substrates are reduced at the cathode in N‐ methyl formamide/LiClO4 as solvent‐supporting‐electrolyte system, and in the presence of arenediazonium salts. Electrochemical pathways are presented to involve a) cascade reactions: hydrogen atom abstraction from a solvent molecule, radical coupling reaction with substrate intermediate, and intramolecular migration of a methylamino group, to provide oxazolones or b) surprising C−C bond cleavage in the substrate radical anion, assisted by a diazonium salt, that evolves to disubstituted arylhydrazides. Abstract : Electrochemical preparative‐scaled concomitant reduction of aromatic 1, 2‐dicarbonyl substrates and arenediazonium tetrafluoroborates in N‐ methylformamide/LiClO4 as solvent‐supporting‐electrolyte system is used to obtain new five‐membered oxazol‐2(3 H )‐one heterocycles and 1, 2‐diaroylhydrazines in good yield.